Indalecio Prieto y la política Española / Abdón Mateos (ed.) - Mateos López, Abdón (1960-)
Bibliografía: p. 317-318 | Contiene textos de Abdón Mateos, Ricardo Miralles, Pedro Luis Angosto, Antonio Rivera, Julio Aróstegui, Santos Juliá, José Carlos Gibaja Velázquez y Luis C. Hernando